(untitled) (Journal of Tourism and Himalayan Adventures, 2020)
This 110 pages brochure book is published by the Department of Geography and Environment, University of Geneva, the Centre for Development and Environment, University of Bern, and the United Nations Environment Program in 2014 and edited by the editors: Bernard Debarbieux (UNIGE), Mari Oiry Varacca (UNIGE), Gilles Rudaz (OFEV), Daniel Maselli (SDC), Thomas Kohler (CDE), Matthias Jurek (UNEP).